Aviation aluminum alloy plate and preparation method thereof

Through the specific method of preparing aerospace aluminum alloy sheets, the problems of existing materials in reducing costs and improving material yield are solved, and the comprehensive improvement of high strength, toughness and corrosion resistance are achieved.

CN119710396APending Publication Date: 2025-03-28SOUTHWEST ALUMINUM GRP

Patent Information

Application Number
CN202411897891.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

While meeting the needs of high strength, toughness and corrosion resistance, existing aerospace aluminum alloy materials are difficult to reduce production costs and improve material yield, especially when preparing ultra-wide thick plates, there is difficulty in engineering.

Method used

A preparation method for aviation aluminum alloy sheet is adopted, including batching, smelting, melt purification, grain refinement, casting, heat treatment, rolling deformation and solid solution aging. By reasonably controlling chemical composition and process parameters, high-purity melt and excellent casting performance are obtained.

Benefits of technology

It achieves high strength, high toughness, excellent corrosion resistance and fatigue resistance, while improving product yield and reducing production costs, meeting the quality needs of the new generation of aluminum alloy materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an aviation aluminum alloy plate and a preparation method thereof. According to the preparation method of the aviation aluminum alloy plate, materials are prepared according to a certain chemical composition, then smelting, melt purification, grain refinement, casting, soaking treatment, rolling deformation and solid solution aging are conducted, and the aviation aluminum alloy plate is obtained. Wherein chemical components are reasonably regulated and controlled, raw materials are controlled, a melt is purified, grains are refined, a proper casting process and a proper soaking treatment process are matched, a proper solid solution aging system is controlled, a high-purity melt, excellent casting performance and a uniform and small cast ingot structure are obtained, and high strength, high toughness and excellent corrosion resistance are achieved; and the method can improve the product yield and reduce the production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metals, and in particular to an aviation aluminum alloy plate and a preparation method thereof. Background Art

[0002] Due to its special chemical composition and strict manufacturing requirements, aviation aluminum alloys have excellent mechanical properties and corrosion resistance, enabling them to serve for a long time in acid rain, marine environment and other extreme environments. Aviation aluminum alloy plates are mainly used for aircraft main wings, fuselages, skins, wall panels, etc.

[0003] As aircraft develop in all aspects of high strength, toughness, damage resistance, reliability, and long life, it is necessary to reduce the cost of engineering applications while meeting the comprehensive performance of materials. After decades of development, the process technology of aviation aluminum alloy materials represented by 7050 aluminum alloy has become very mature, and it is difficult to reduce the cost of raw materials and manufacturing by optimizing processes and processes. In order to reduce the cost of engineering applications, it can only be achieved by improving the toughness of the material or reducing the density of the alloy material. Under the current process conditions, the cost of melting and casting low-density alloys is extremely high and the engineering difficulty is relatively large.

[0004] In order to meet the comprehensive performance requirements of the product, it is necessary to develop and optimize the chemical composition, melt purification, casting process, rolling deformation, etc. High strength, toughness and long life performance require a high degree of alloying and complex proportions, and large-scale products require the development of extreme sizes, which requires the melt purity, ingot uniformity and density and processing process to be controlled at an extremely high level. At the same time, it also makes it difficult to explore and match the control window of melt purification, casting and processing technology, especially for ultra-wide and thick plates, which are more difficult to engineer. Summary of the invention

[0005] In view of this, the present invention provides an aviation aluminum alloy plate and its preparation method. The preparation method of the present invention can obtain a high-purity melt and excellent casting performance, and the product has high strength, high toughness, excellent corrosion resistance, and fatigue resistance, and can improve the product yield and reduce production costs.

[0006] The present invention provides a method for preparing an aviation aluminum alloy plate, comprising the following steps:

[0007] S1. Ingredients:

[0008] The raw materials are batched according to the target alloy composition;

[0009] in,

[0010] In terms of mass percentage, the target alloy comprises:

[0011] Si: ≤0.04%;

[0012] Fe: ≤0.07%;

[0013] Cu: 1.7%~2.0%;

[0014] Mn: ≤0.02%;

[0015] Mg: 1.8%~2.2%;

[0016] Cr: ≤0.02%;

[0017] Zn: 7.7%~8.5%;

[0018] Ti: ≤0.05%;

[0019] Zr: 0.05%~0.15%;

[0020] Be: 0.0005%~0.005%;

[0021] Na: ≤0.0003%;

[0022] Single impurity: ≤0.03%;

[0023] The balance is Al;

[0024] The raw materials include: aluminum ingots, copper, magnesium ingots, zinc ingots, Al-Cu master alloys, Al-Zr master alloys, Al-Ti master alloys, and Al-Be master alloys;

[0025] S2. Melting:

[0026] The raw materials are smelted to obtain an alloy melt;

[0027] S3, melt purification:

[0028] In the furnace, the granular refining agent is first blown into the melt by gas medium 1 for powder spray refining in the furnace; then the melt is transferred to the holding furnace, and the melt is refined by gas medium 2 through the air-permeable bricks at the bottom of the furnace, and then allowed to stand after refining; then the melt is degassed and refined by the rotary degassing device; then, it is filtered to obtain a purified melt;

[0029] in,

[0030] The gas medium 1 is argon, and the purity of the argon is ≥ 99.999%;

[0031] The gas medium 2 is argon gas, and the purity of the argon gas is ≥ 99.999%;

[0032] The gas used for degassing and refining is an argon-chlorine mixed gas; the purity of the gas is ≥99.999%; the volume proportion of argon in the argon-chlorine mixed gas is 95% to 99.5%;

[0033] S4. Grain refinement:

[0034] Grain refinement was performed online using Al-3Ti-0.15C wire;

[0035] S5. Casting:

[0036] Casting the alloy melt obtained in step S4 to obtain an ingot;

[0037] The casting conditions are as follows: casting speed 40-55 mm / min, water flow 30-60 m 3 / h. Root, aluminum liquid temperature at the end of the flow plate is 695~715℃, water temperature is 22~28℃, and wiper height is 200~500mm;

[0038] S6. Heat treatment:

[0039] The ingot obtained in step S5 is subjected to primary soaking treatment and secondary soaking treatment in sequence;

[0040] The conditions of the first-stage heat treatment are as follows: heating rate 30-80°C / h, holding temperature 380-420°C, holding time 5-12h;

[0041] The conditions of the secondary heat treatment are as follows: heating rate 5-20°C / h, holding temperature 465-475°C, holding time 30-50h;

[0042] S7, rolling deformation:

[0043] The ingot obtained in step S6 is heated, rolled into a plate, and stretched to obtain a plate;

[0044] S8, solution aging:

[0045] The plate obtained in step S7 is subjected to solution treatment, stretching treatment, and aging treatment to obtain an aviation aluminum alloy plate.

[0046] Preferably, step S2 specifically includes:

[0047] The aluminum ingot, copper and zinc ingot are heated and melted, and then magnesium ingot, Al-Cu master alloy, Al-Zr master alloy, Al-Ti master alloy and Al-Be master alloy are added, smelted and slag removed to obtain alloy melt;

[0048] The heating and melting temperature is 730-770°C.

[0049] Preferably, in step S3, when the melt is refined by using gas medium 2 through the furnace bottom air-permeable bricks, the melt temperature during refining is 730-750° C., the refining time is 20-40 min; and the standing time is ≥45 min.

[0050] Preferably, in step S3, the filtration is performed using a 30ppi+50ppi or 40ppi+60ppi ceramic filter plate.

[0051] Preferably, in step S4, the amount of the Al-3Ti-0.15C wire used is 2.0-4.0 kg / t.

[0052] Preferably, in step S5, the specifications of the cast ingot are as follows: thickness 400-520 mm, width 1500-2250 mm, length 4000-8000 mm.

[0053] Preferably, in step S6:

[0054] The heating temperature is 400-450°C;

[0055] The stretching ratio of the stretching treatment is 1% to 3%.

[0056] Preferably, in step S7:

[0057] The solution treatment temperature is 465-480°C, and the holding time is 90-450min; the solution quenching transfer time is less than 15s, and the quenching water temperature is 10-30°C;

[0058] The stretching ratio of the stretching treatment is 0.5% to 1.5%.

[0059] Preferably, in step S7, the artificial aging treatment is performed 2 to 48 hours after solution quenching;

[0060] The artificial aging treatment includes two-stage aging treatment; wherein, the conditions of the first-stage aging treatment are: temperature 121° C., time 4 to 6 hours; the conditions of the second-stage aging treatment are: temperature 148 to 160° C., time 10 to 30 hours.

[0061] The present invention also provides an aviation aluminum alloy plate, which is prepared by the preparation method described in the above technical solution.

[0062] The preparation method of the aviation aluminum alloy plate provided by the present invention is to prepare ingredients according to a certain chemical composition, and then carry out smelting, melt purification, grain refinement, casting, soaking treatment, rolling deformation, and solid solution aging to obtain the aviation aluminum alloy plate. Among them, the chemical composition is reasonably regulated, the raw materials are controlled, the melt purification, grain refinement, and the appropriate casting process and soaking treatment process are matched, and the appropriate solid solution aging system is controlled to obtain a high-purity melt, excellent casting performance and uniform and fine ingot structure, and achieve high strength, high toughness, excellent corrosion resistance, and fatigue resistance; and the method of the present invention can improve the product yield rate and reduce production costs.

[0063] The test results show that the grain size of the ingot obtained by the casting method of the present invention reaches 2.5 grade; the hydrogen content of the melt is below 0.072mL / 100gAl, and the slag content is below 0.007m 2 / kg or less, a high-cleanliness melt; tensile strength is above 551MPa, yield strength is above 503MPa, fracture toughness is above 32MPa·m 1 / 2 Above, achieving high strength and high toughness; in the stress corrosion test, the sample did not crack for 30 days, and reached EA level in the exfoliation corrosion test, showing excellent corrosion resistance; the fatigue performance test can reach more than 200,000 times, showing excellent fatigue resistance; the flaw detection meets the A level and the quality is relatively high; in addition, the casting forming rate reaches more than 90%, which improves the product yield rate. DETAILED DESCRIPTION

[0064] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0065] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0066] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0067] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0068] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 40-55mm / min means that the units of the left endpoint "40" and the right endpoint "55" are both mm / min.

[0069] The present invention provides a method for preparing an aviation aluminum alloy plate, comprising the following steps:

[0070] S1. Ingredients:

[0071] The raw materials are batched according to the target alloy composition;

[0072] in,

[0073] In terms of mass percentage, the target alloy comprises:

[0074] Si: ≤0.04%;

[0075] Fe: ≤0.07%;

[0076] Cu: 1.7%~2.0%;

[0077] Mn: ≤0.02%;

[0078] Mg: 1.8%~2.2%;

[0079] Cr: ≤0.02%;

[0080] Zn: 7.7%~8.5%;

[0081] Ti: ≤0.05%;

[0082] Zr: 0.05%~0.15%;

[0083] Be: 0.0005%~0.005%;

[0084] Na: ≤0.0003%;

[0085] Single impurity: ≤0.03%;

[0086] The balance is Al;

[0087] The raw materials include: aluminum ingots, copper, magnesium ingots, zinc ingots, Al-Cu master alloys, Al-Zr master alloys, Al-Ti master alloys, and Al-Be master alloys;

[0088] S2. Melting:

[0089] The raw materials are smelted to obtain an alloy melt;

[0090] S3, melt purification:

[0091] In the furnace, the granular refining agent is first blown into the melt by gas medium 1 for powder spray refining in the furnace; then the melt is transferred to the holding furnace, and the melt is refined by gas medium 2 through the air-permeable bricks at the bottom of the furnace, and then allowed to stand after refining; then the melt is degassed and refined by the rotary degassing device; then, it is filtered to obtain a purified melt;

[0092] in,

[0093] The gas medium 1 is argon, and the purity of the argon is ≥ 99.999%;

[0094] The gas medium 2 is argon gas, and the purity of the argon gas is ≥ 99.999%;

[0095] The gas used for degassing and refining is an argon-chlorine mixed gas; the purity of the gas is ≥99.999%; the volume proportion of argon in the argon-chlorine mixed gas is 95% to 99.5%;

[0096] S4. Grain refinement:

[0097] Grain refinement was performed online using Al-3Ti-0.15C wire;

[0098] S5. Casting:

[0099] Casting the alloy melt obtained in step S4 to obtain an ingot;

[0100] The casting conditions are as follows: casting speed 40-55 mm / min, water flow 30-60 m 3 / h. Root, aluminum liquid temperature at the end of the flow plate is 695~715℃, water temperature is 22~28℃, and wiper height is 200~500mm;

[0101] S6. Heat treatment:

[0102] The ingot obtained in step S5 is subjected to primary soaking treatment and secondary soaking treatment in sequence;

[0103] The conditions of the first-stage heat treatment are as follows: heating rate 30-80°C / h, holding temperature 380-420°C, holding time 5-12h;

[0104] The conditions of the secondary heat treatment are as follows: heating rate 5-20°C / h, holding temperature 465-475°C, holding time 30-50h;

[0105] S7, rolling deformation:

[0106] The ingot obtained in step S6 is heated, rolled into a plate, and stretched to obtain a plate;

[0107] S8, solution aging:

[0108] The plate obtained in step S7 is subjected to solution treatment, stretching treatment, and aging treatment to obtain an aviation aluminum alloy plate.

[0109] With the development of the aviation industry, large-scale, stability and economy have become the current development trend of aluminum alloys. However, in order to meet the comprehensive performance of materials and have long-term service capabilities in extreme environments, existing materials have to sacrifice the demand for lighter weight. The aviation aluminum alloy proposed in the present invention has higher strength and damage resistance than current aerospace materials, and has better comprehensive performance. While improving the strength and toughness of the material, it also increases the damage resistance of the material. When using the same thickness of the plate, the strength is increased by more than 10% based on the 7050 alloy, and the damage resistance (fatigue and corrosion resistance) is greatly improved, thereby reducing the use cost of aircraft.

[0110] [About step S1]:

[0111] S1. Batching: batching the raw materials according to the target alloy composition.

[0112] In the present invention, the target alloy comprises, by mass percentage:

[0113] Si: ≤0.04%;

[0114] Fe: ≤0.07%;

[0115] Cu: 1.7%~2.0%;

[0116] Mn: ≤0.02%;

[0117] Mg: 1.8%~2.2%;

[0118] Cr: ≤0.02%;

[0119] Zn: 7.7%~8.5%;

[0120] Ti: ≤0.05%;

[0121] Zr: 0.05%~0.15%;

[0122] Be: 0.0005%~0.005%;

[0123] Na: ≤0.0003%;

[0124] Single impurity: ≤0.03%;

[0125] The balance is Al.

[0126] Compared with 7050 aluminum alloy, the present invention increases the Zn content to ensure the tensile properties of the material; reduces the Cu content to ensure the strength and toughness matching of the material, while optimizing the alloy hardenability, and also reduces the T phase residue from the source to improve the fracture toughness of the plate, while controlling its lower limit to ensure its corrosion resistance, especially stress corrosion performance; in addition, strictly controls the Si and Fe contents to ensure the material's impact toughness, fracture toughness, static fatigue strength and torsional strength and other properties. The overall chemical composition is shown above.

[0127] in,

[0128] The Cu content can be specifically 1.7%, 1.8%, 1.9%, 2.0%. The Mg content can be specifically 1.8%, 1.9%, 2.0%, 2.1%, 2.2%. The Zn content can be specifically 7.7%, 7.8%, 7.9%, 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%. The Zr content can be specifically 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%. The Be content can be specifically 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%.

[0129] In one embodiment of the present invention, the alloy product composition is as follows: Si 0.03%, Fe 0.05%, Cu 1.92%, Mn 0.01%, Cr 0.01%, Mg 2.1%, Zn 8.25%, Ti 0.03%, Zr 0.12%, Be 0.001%, Na 0.0001%, single impurity ≤ 0.03%, the balance is Al. In another embodiment of the present invention, the alloy product composition is as follows: Si 0.03%, Fe 0.05%, Cu 1.90%, Mn 0.01%, Cr 0.01%, Mg 2.13%, Zn 8.30%, Ti0.03%, Zr 0.12%, Be 0.0009%, Na 0.0001%, single impurity ≤ 0.03%, the balance is Al. In another embodiment of the present invention, the alloy product has the following composition: Si 0.02%, Fe 0.04%, Cu 1.93%, Mn 0.01%, Cr0.01%, Mg 2.10%, Zn 8.28%, Ti 0.03%, Zr 0.12%, Be 0.0012%, Na 0.0001%, single impurity ≤0.03%, and the balance is Al.

[0130] In the present invention, the raw materials include: aluminum ingots, copper, magnesium ingots, zinc ingots, Al-Cu master alloys, Al-Zr master alloys, Al-Ti master alloys, and Al-Be master alloys. The present invention uses aluminum ingots with higher purity and other raw materials with better uniformity to ensure that impurities and trace elements such as Si, Fe, Mn, Cr, and Na are controlled at extremely low levels, and better meet the casting performance and product comprehensive performance requirements. Among them, the aluminum ingot is preferably an original aluminum ingot with a grade of Al99.95 or above. Copper is specifically a copper plate, preferably a copper plate with a grade of Cu99.95 or above. The magnesium ingot is preferably a magnesium ingot with a grade of Mg99.9 or above. The zinc ingot is preferably a zinc ingot with a grade of Zn99.99 or above. All raw materials used in the gold alloy cannot use waste materials and are produced from original aluminum ingots with a grade of Al99.70 or above. The Al-Zr master alloy is preferably an AlZr4 master alloy. The Al-Ti master alloy is preferably an AlTi4 master alloy. The Al-Be master alloy is preferably an AlBe3 master alloy. The Al-Cu master alloy is preferably an AlCu40 master alloy. In the present invention, in addition to the above-mentioned metal and alloy raw materials, primary waste is also used for batching. The present invention has no special restrictions on the type and source of the primary waste, and the primary waste commonly used in the process of preparing aluminum alloys in this field can be used. The present invention has no special restrictions on the amount of the primary waste, and the target alloy composition can be met according to the conventional addition ratio in the process of preparing aluminum alloys in this field. The raw materials used in the present invention must ensure dryness and pollution-free.

[0131] [About step S2]:

[0132] S2, smelting: smelting the raw materials to obtain an alloy melt;

[0133] In the present invention, step S2 preferably specifically comprises: heating and melting aluminum ingots, copper and zinc ingots, then adding magnesium ingots, Al-Cu master alloys, Al-Zr master alloys, Al-Ti master alloys and Al-Be master alloys, smelting, removing slag, and obtaining an alloy melt.

[0134] in,

[0135] The heating and melting temperature is preferably 730-770°C, specifically 730°C, 735°C, 740°C, 745°C, 746°C, 750°C, 753°C, 755°C, 760°C, 765°C, 770°C. After the aluminum ingot, copper and zinc ingot are completely melted, magnesium ingot and intermediate alloy are added, stirred and slag removed. In addition, sampling analysis and component adjustment are also carried out; specifically, the chemical composition of the alloy melt is sampled and analyzed, and compared with the component composition of the target alloy. If the two are consistent, subsequent refining and other steps are carried out. If the two are inconsistent, materials need to be added to the raw material liquid to adjust the composition. After the two are consistent, subsequent refining and other steps are carried out.

[0136] [About step S3]:

[0137] S3, melt purification: firstly, gas medium 1 is used to blow the granular refining agent into the melt in the furnace for powder spray refining in the furnace; then the melt is transferred to the insulation furnace, and the melt is refined by gas medium 2 through the air-permeable bricks at the bottom of the furnace, and then allowed to stand after refining; then the melt is degassed and refined by a rotary degassing device; then, it is filtered to obtain a purified melt.

[0138] In the present invention, the gas medium 1 is first used in the furnace to blow the particle refining agent into the melt for powder spray refining in the furnace. The gas medium 1 is argon; the purity of the argon is ≥ 99.999% (i.e., high-purity argon). The time for the powder spray refining is preferably 10 to 30 minutes, specifically 10 minutes, 20 minutes, 30 minutes, and more preferably 20 minutes.

[0139] In the present invention, after the powder spray refining in the furnace is qualified, it is transferred to the insulation furnace, and the melt is refined by gas medium 2 through the air-permeable bricks at the bottom of the furnace. Wherein, the gas medium 2 is argon; the purity of the argon is ≥99.999% (i.e. high-purity argon). The melt temperature during the refining is 730-750°C, specifically 730°C, 735°C, 740°C, 745°C, 746°C, 748°C, 750°C. The refining time is preferably 20-40min, specifically 20min, 30min, 40min, and more preferably 30min. After the above refining, it is allowed to stand to allow the removed slag to fully float or precipitate. The standing time is preferably ≥45min. After the above refining, the hydrogen content of the melt is controlled to be ≤0.20mL / 100gAl.

[0140] In the present invention, after the above-mentioned bottom ventilation refining, degassing and refining are carried out by a rotary degassing device. In the present invention, the gas used for the degassing and refining is an argon-chlorine mixed gas. The purity of the gas used is ≥99.999%. Among them, the volume proportion of argon in the argon-chlorine mixed gas is 95% to 99.5%, specifically 95%, 96%, 97%, 98%, 99%. After the above-mentioned degassing and refining, the hydrogen content of the melt is reduced to ≤0.08mL / 100gAl.

[0141] In the present invention, after the above refining, filtration is performed. In the present invention, the filtration is preferably performed by 30ppi+50ppi, or 40ppi+60ppi ceramic filter plates. The maximum filtration amount does not exceed 70 tons. After filtration, a purified melt is obtained.

[0142] [About step S4]:

[0143] S4. Grain refinement: Al-3Ti-0.15C wire is used online for grain refinement.

[0144] Generally, an intermediate alloy containing Ti and B or an intermediate alloy containing Ti and C is added to aluminum alloy to refine the cast grains, but if the content is too high, aggregated compounds will be formed, and the B-containing refiner is easy to form TiB2 particle aggregates, which become the source of ingot cracks; the present invention has a high degree of alloying, a large ingot specification, and a greater difficulty in forming. At the same time, it requires an extremely uniform and dense structure, and requires a rapid solidification method, which further causes an increase in casting stress; the present invention uses Al-3Ti-0.15C wire for grain refinement, which is beneficial for the present invention to obtain a uniform and dense alloy structure.

[0145] In the present invention, the amount of the Al-3Ti-0.15C wire is preferably 2.0-4.0 kg / t, specifically 2.0 kg / t, 2.1 kg / t, 2.2 kg / t, 2.3 kg / t, 2.4 kg / t, 2.5 kg / t, 2.6 kg / t, 2.7 kg / t, 2.8 kg / t, 2.9 kg / t, 3.0 kg / t, 3.1 kg / t, 3.2 kg / t, 3.3 kg / t, 3.4 kg / t, 3.5 kg / t, 3.6 kg / t, 3.7 kg / t, 3.8 kg / t, 3.9 kg / t, and 4.0 kg / t.

[0146] [About step S5]:

[0147] S5, casting: casting the alloy melt obtained in step S4 to obtain an ingot.

[0148] In order to obtain an ingot with better performance, a faster casting speed is generally used, which can make the ingot grains finer and the ingot density higher, but the alloying degree is higher, the melt fluidity becomes worse, and the solidification process is prone to insufficient shrinkage. Too high a speed will increase the tendency of cracks; with the increase of cooling intensity, the size of the primary crystal compound can be refined and the regional segregation can be reduced. In order to obtain good ingot quality and comprehensive product performance, the present invention controls the casting conditions as follows: casting speed 40-55mm / min, water flow 30-60m 3 / h. Root, aluminum liquid temperature at the end of the flow plate is 695-715°C, water temperature is 22-28°C, and wiper height is 200-500mm. Among them, the casting speed can be specifically 40mm / min, 41mm / min, 42mm / min, 43mm / min, 44mm / min, 45mm / min, 46mm / min, 47mm / min, 48mm / min, 49mm / min, 50mm / min, 51mm / min, 52mm / min, 53mm / min, 54mm / min, 55mm / min. The water flow refers to the cooling water flow, which can be specifically 30m 3 / h.root, 35m 3 / h.root, 40m 3 / h.root, 45m3 / h.root, 50m 3 / h.root, 55m 3 / h.root, 60m 3 / h.root. The aluminum liquid temperature at the end of the flow plate can be 695℃, 696℃, 697℃, 698℃, 699℃, 700℃, 701℃, 702℃, 703℃, 704℃, 705℃, 706℃, 707℃, 708℃, 709℃, 710℃, 711℃, 712℃, 713℃, 714℃, 715℃. The water temperature, i.e. the cooling water temperature, can be 22℃, 23℃, 24℃, 25℃, 26℃, 27℃, 28℃. The wiper height can be 200mm, 250mm, 300mm, 350mm, 400mm, 410mm, 450mm, 500mm. After the above casting, an ingot is obtained.

[0149] In the present invention, the specifications of the cast ingot are preferably as follows: thickness 400-520 mm, width 1500-2250 mm, length 4000-8000 mm.

[0150] [About step S6]:

[0151] S6. Soaking treatment: The ingot obtained in step S5 is subjected to primary soaking treatment and secondary soaking treatment in sequence.

[0152] In the present invention, the conditions of the primary heat treatment are as follows: heating rate 30-80°C / h, insulation temperature 380-420°C, insulation time 5-12h. Wherein, the heating rate can be specifically 30°C / h, 35°C / h, 40°C / h, 45°C / h, 50°C / h, 55°C / h, 60°C / h, 65°C / h, 70°C / h, 75°C / h, 80°C / h. The insulation temperature can be specifically 380°C, 385°C, 390°C, 395°C, 400°C, 405°C, 410°C, 415°C, 420°C. The insulation time can be specifically 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h. In the present invention, the heating time is preferably 8 to 15 hours, specifically 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, and 15 hours. In the present invention, the heating temperature is preferably 400 to 450°C, specifically 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C, and 450°C; the heating temperature is higher than the insulation temperature, which is called differential temperature heating; the heating temperature is the same as the insulation temperature, which is called isothermal heating; the present invention adopts differential temperature heating, which can achieve rapid temperature reaching, save energy consumption, and improve production efficiency.

[0153] In the present invention, the conditions of the secondary heat treatment are as follows: heating rate 5-20°C / h, insulation temperature 465-475°C, insulation time 30-50h. Wherein, the heating rate can be specifically 5°C / h, 10°C / h, 15°C / h, 20°C / h. The insulation temperature can be specifically 465°C, 466°C, 467°C, 468°C, 469°C, 470°C, 471°C, 472°C, 473°C, 474°C, 475°C. The insulation time can be specifically 30h, 35h, 40h, 45h, 50h. In the present invention, the heating time is preferably 5-20h, specifically 5h, 10h, 15h, 20h. In the present invention, the heating temperature is preferably 470-480°C, specifically 470°C, 471°C, 472°C, 473°C, 474°C, 475°C, 476°C, 477°C, 478°C, 479°C, 480°C; that is, differential temperature equalization is adopted. In the present invention, a primary equalization treatment and a secondary equalization treatment are carried out in sequence, that is, after the primary equalization treatment is completed, the temperature is directly raised on the basis of the secondary equalization treatment. The present invention can eliminate the ingot stress, reduce the ingot segregation, make the residual phase generated in the casting process fully dissolved into the matrix, and make the strengthening phase evenly filled and dissolved.

[0154] [Regarding step S7]:

[0155] S7, rolling deformation: the ingot obtained in step S6 is heated, rolled into a plate, and stretched to obtain a plate.

[0156] In the present invention, the heating temperature is preferably 400-450°C, specifically 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C, 450°C. After heating to the above temperature, rolling is performed to obtain a plate. In order to obtain a better exfoliation corrosion effect, the temperature during rolling is appropriately controlled to be lower, preferably 400-430°C, specifically 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C.

[0157] In the present invention, the thickness of the plate is preferably 20-152mm, specifically 20mm, 25mm, 30mm, 35mm, 40mm, 45mm, 50mm, 55mm, 60mm, 65mm, 70mm, 75mm, 80mm, 85mm, 90mm, 100mm, 105mm, 110mm, 115mm, 120mm, 125mm, 130mm, 135mm, 140mm, 145mm, 150mm, 152mm.

[0158] In the present invention, in order to control the plate shape and reduce stress, stretching is performed after rolling. The stretching rate of the stretching is preferably 1% to 3%, specifically 1%, 1.5%, 2%, 2.5%, 3%. The present invention also needs to perform a second stretching after subsequent solution quenching, see below for details.

[0159] [About step S8]:

[0160] S8, solution treatment and aging: the plate obtained in step S7 is subjected to solution treatment, stretching treatment and aging treatment to obtain an aviation aluminum alloy plate.

[0161] In the present invention, the temperature of the solution treatment is preferably 465-480°C, specifically 465°C, 466°C, 467°C, 468°C, 469°C, 470°C, 471°C, 472°C, 473°C, 474°C, 475°C, 476°C, 477°C, 478°C, 479°C, 480°C. The holding time of the solution treatment is preferably 90-450min, specifically 90min, 100min, 150min, 200min, 250min, 300min, 350min, 400min, 450min. In the present invention, after the above-mentioned solution treatment, the steel is transferred for quenching, wherein the quenching transfer time is preferably less than 15s; the quenching water temperature is preferably 10-30°C, specifically 10°C, 15°C, 20°C, 25°C, 30°C.

[0162] In the present invention, after the solution quenching, a stretching treatment is performed, wherein the stretching ratio of the stretching treatment is preferably 0.5% to 1.5%, specifically 0.5%, 1.0%, or 1.5%.

[0163] In the present invention, after the above-mentioned stretching treatment, artificial aging treatment is carried out. The timing of the artificial aging treatment is 2 to 48 hours after solution quenching. In the present invention, the artificial aging treatment includes two-stage aging treatment, wherein the conditions for the first-stage aging are preferably: temperature 121°C, time 4 to 6 hours, specifically 4 hours, 5 hours, and 6 hours. The conditions for the second-stage aging are preferably: temperature 148 to 160°C, time 10 to 30 hours; wherein the temperature can specifically be 148°C, 150°C, 155°C, and 160°C; the time can specifically be 10 hours, 15 hours, 20 hours, 25 hours, and 30 hours. After the above treatment, an aviation aluminum alloy sheet is obtained.

[0164] The present invention adopts the above-mentioned solid solution aging system, which can effectively improve the strength and toughness matching of the material, reduce the diffusion of Cu into the aluminum cladding layer, obtain excellent tensile strength, and improve the corrosion resistance of the alloy.

[0165] After the above solution aging, the present invention preferably further performs post-treatment, such as sawing, etc., to obtain a product.

[0166] In order to meet the requirements of high toughness and damage resistance of materials, it is necessary to reasonably design the alloy composition and proportion, improve the quality of ingots and strictly control the processing process, but it also brings about the problems of great difficulty in controlling the purity of the melt, poor casting performance, low production efficiency and mismatch of processing performance. Compared with 7050 aluminum alloy, the alloy casting molding, ingot internal structure and product performance stability control of the present invention are more difficult, which seriously restricts the engineering application of the aluminum alloy material. It is difficult to guarantee the product requirements for the existing technology of the aluminum alloy. The preparation method of the aviation aluminum alloy plate provided by the present invention is prepared according to a certain chemical composition, and then smelting, melt purification, grain refinement, casting, soaking treatment, rolling deformation, and solid solution aging are carried out to obtain the aviation aluminum alloy plate. Among them, the chemical composition is reasonably regulated, the raw materials are controlled, the melt purification, grain refinement and the appropriate casting process and soaking treatment process are matched, and the appropriate solid solution aging system is controlled to obtain a high purity melt, excellent casting performance and uniform and fine ingot structure, and achieve high strength, high toughness and excellent corrosion resistance; and the method of the present invention can improve the product yield rate and reduce production costs. The obtained products can meet the quality requirements of the new generation of aluminum alloy materials.

[0167] The test results show that the grain size of the ingot obtained by the casting method of the present invention reaches 2.5 grade; the hydrogen content of the melt is below 0.072mL / 100gAl, and the slag content is below 0.007m 2 / kg or less, a high-cleanliness melt; tensile strength is above 551MPa, yield strength is above 503MPa, fracture toughness is above 32MPa·m 1 / 2 Above, achieving high strength and high toughness; in the stress corrosion test, the sample did not crack for 30 days, and reached EA level in the exfoliation corrosion test, showing excellent corrosion resistance; the fatigue performance test can reach more than 200,000 times, showing excellent fatigue resistance; the flaw detection meets the A level and the quality is relatively high; in addition, the casting forming rate reaches more than 90%, which improves the product yield rate.

[0168] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0169] Example 1

[0170] Specifications: Ingot specifications are 520mm thick × 1600mm wide × 4000mm long; plate thickness is 50mm.

[0171] S1. Ingredients:

[0172] Raw materials: Al99.95 grade aluminum ingot, Al99.95 grade copper plate, Al99.9 grade magnesium ingot, Al99.99 grade zinc ingot, AlCu40, AlBe3, AlZr4, AlTi4 intermediate alloys produced from Al99.70 grade aluminum ingot.

[0173] Mix ingredients according to target composition: Please refer to the test results below for ingredient composition.

[0174] S2. Melting:

[0175] The aluminum ingot, copper plate and zinc ingot are heated and melted at a melting temperature of 746°C. After the aluminum ingot, copper and zinc ingot are completely melted, magnesium ingot and various intermediate alloys are added, stirred and slag removed. During this period, sampling analysis and composition adjustment are carried out.

[0176] S3, melt purification:

[0177] After the ingredients in step S2 are adjusted, high-purity argon (purity ≥ 99.999%) is used in the furnace to blow the granular refining agent (originating from Zhengzhou Xisheng) into the melt and refine for 20 minutes; after the powder spray refining in the furnace is qualified, it is transferred to the insulation furnace, and the melt is refined with high-purity argon (purity ≥ 99.999%) through the breathable bricks at the bottom of the furnace. During the refining, the melt temperature is 745°C, the refining time is 30 minutes, and it is allowed to stand for 45 minutes after refining. The hydrogen content of the melt after refining is 0.18mL / 100gAl. After refining through the bottom of the furnace, it is refined with a high-purity argon-chlorine mixed gas (the volume proportion of argon in the mixed gas is 98%) through a rotary degassing device. The hydrogen content of the melt after treatment is 0.072mL / 100gAl. After the above-mentioned online degassing, a 40ppi+60ppi foam ceramic filter plate is used to filter the melt, and the slag content after filtration is 0.007m 2 / kg.

[0178] S4. Grain refinement:

[0179] Al-3Ti-0.15C wire was used online for grain refinement, with a dosage of 3.0 kg / t.

[0180] S5. Casting:

[0181] The alloy melt obtained in step S4 is cast to obtain an ingot.

[0182] Casting conditions are as follows: casting speed 48mm / min, water flow 38m 3 / h. root, the aluminum liquid temperature at the end of the flow plate is 695℃, the water temperature is 26℃, and the wiper height is 450mm.

[0183] S6. Heat treatment:

[0184] Step S4: After the casting is completed, the ingot is immediately subjected to a soaking treatment, specifically, a primary soaking treatment and a secondary soaking treatment are performed in sequence.

[0185] The conditions for the first-stage heat treatment are as follows: heating rate 40℃ / h, heating time 10h, holding temperature 410℃, holding time 8h. The conditions for the second-stage heat treatment are as follows: heating rate 7℃ / h, heating time 10h, holding temperature 470℃, holding time 40h.

[0186] S7, rolling deformation:

[0187] The ingot obtained in step S6 was heated to 430°C and then rolled to obtain a plate with a thickness of 50 m. Then, it was stretched to a stretching ratio of 1.5%.

[0188] S8, solution aging:

[0189] The plate obtained in step S7 is subjected to solution treatment, and the process is as follows: heating temperature is 475° C., and heat preservation is performed for 300 min; then quenching is performed in 20° C. water, and the quenching transfer time is 12 s.

[0190] After the above-mentioned solution treatment, a stretching treatment was performed with a stretching ratio of 1.2%.

[0191] After the above-mentioned stretching treatment, artificial aging treatment is carried out: specifically, it is carried out after quenching for 8 hours, the first-level aging is 121°C+4h, and the second-level aging is 154°C+16h.

[0192] After the above processes, the plates are sawn to obtain T7451 state 50mm thickness specification plates, flaw detection and performance testing.

[0193] Quality Inspection :

[0194] Performance indicators:

[0195] The tensile strength in three directions (L, LT, ST) is ≥525MPa, and the yield strength in three directions (L, LT, ST) is ≥456MPa. Fracture toughness: thickness ≤102mm, LT direction should be no less than Thickness>102~153mm, LT direction should be no less than For stress corrosion C-ring specimens, when a load of 310MPa was applied, there was no stress corrosion cracking after 30 days of testing; the exfoliation corrosion grade was EA. Fatigue life: Under the maximum stress of 310MPa, the minimum number of cycles for each test was 90,000 times, and the minimum average of 4 specimens was 120,000 times.

[0196] Test results:

[0197] (1) Ingot low magnification: Grain size 2.5; the test method is GB / T3246.2 "Test Methods for Microstructure of Deformed Aluminum and Aluminum Alloy Products - Part 2 Test Methods for Microstructure";

[0198] (2) Chemical composition: Si 0.03%, Fe 0.05%, Cu 1.92%, Mn 0.01%, Cr 0.01%, Mg2.1%, Zn 8.25%, Ti 0.03%, Zr 0.12%, Be 0.001%, Na 0.0001%, single impurity ≤ 0.03%, balance Al. The detection method is GB / T 20975 "Analysis Method of Aluminum Alloy" and GB / T7999 "Photoelectric Direct Reading Emission Spectroscopy Analysis Method for Aluminum and Aluminum Alloy";

[0199] (3) Hydrogen content: 0.072mL / 100gAl; the detection method is YS / T600 "Closed-circuit method for measuring hydrogen in liquid state of aluminum and aluminum alloy"; slag content: 0.007m 2 / kg, the detection method is YS / T1681 "Offline slag content detection method for deformed aluminum and aluminum alloy melt";

[0200] (4) Mechanical properties: tensile strength 589MPa, yield strength 553MPa, elongation 14%. The test method is GB / T16865 "Test specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products".

[0201] (5) Fracture toughness: 42.75 MPa·m 1 / 2 The test method is GB / T 4161 "Plane Strain Fracture Toughness K of Metallic Materials" IC Test Methods

[0202] (6) Stress corrosion resistance: The sample did not crack after 30 days of testing. The testing method was HB / 5259 "Stress corrosion test method for aluminum alloy C ring sample";

[0203] (7) Exfoliation corrosion: EA level, the detection method is HB / 5455 "Test method for exfoliation corrosion of aluminum alloys".

[0204] (8) Fatigue performance: more than 200,000 times. The test method is HB / 5287 "Axial Loading Fatigue Test Method for Metal Materials".

[0205] (9) Flaw detection: Meets Class A. The detection method is GB / T 6519 “Ultrasonic Testing Method for Deformed Aluminum and Magnesium Alloy Products”.

[0206] (10) Yield rate: 12 ingots were cast continuously, with a casting yield rate of 91.67%.

[0207] It can be seen that all performances of the product of Example 1 meet the index requirements; in addition, the casting yield is high when the experiment is repeated continuously according to Example 1.

[0208] Example 2

[0209] Specifications: Ingot specifications are 520mm thick × 1600mm wide × 4000mm long; plate thickness is 80mm.

[0210] S1. Ingredients:

[0211] Raw materials: Al99.95 grade aluminum ingot, Al99.95 grade copper plate, Al99.9 grade magnesium ingot, Al99.99 grade zinc ingot, AlCu40, AlBe3, AlZr4, AlTi4 intermediate alloys produced from Al99.70 grade aluminum ingot.

[0212] Mix ingredients according to target composition: Please refer to the test results below for ingredient composition.

[0213] S2. Melting:

[0214] The aluminum ingot, copper plate and zinc ingot are heated and melted at a melting temperature of 750°C. After the aluminum ingot, copper and zinc ingot are completely melted, magnesium ingot and various intermediate alloys are added, stirred and slag removed. During this period, sampling analysis and composition adjustment are carried out.

[0215] S3, melt purification:

[0216] After the ingredients in step S2 are adjusted, high-purity argon (purity ≥ 99.999%) is used in the furnace to blow the granular refining agent (derived from Perico) into the melt and refine for 20 minutes; after the powder spray refining in the furnace is qualified, it is transferred to the insulation furnace, and the melt is refined with high-purity argon (purity ≥ 99.999%) through the breathable bricks at the bottom of the furnace. During the refining, the melt temperature is 748°C, the refining time is 30 minutes, and it is allowed to stand for 45 minutes after refining. The hydrogen content of the melt after refining is 0.16mL / 100gAl. After refining through the bottom of the furnace, it is refined with a high-purity argon-chlorine mixed gas (the volume proportion of argon in the mixed gas is 98%) through a rotary degassing device. The hydrogen content of the melt after treatment is 0.071mL / 100gAl. After the above-mentioned online degassing, a 30ppi+50ppi foam ceramic filter plate is used for melt filtration. The slag content after filtration is 0.006m 2 / kg.

[0217] S4. Grain refinement:

[0218] Al-3Ti-0.15C wire was used online for grain refinement, with a dosage of 3.0 kg / t.

[0219] S5. Casting:

[0220] The alloy melt obtained in step S4 is cast to obtain an ingot.

[0221] Casting conditions are as follows: casting speed 48mm / min, water flow 38m 3 / h. root, the aluminum liquid temperature at the end of the flow plate is 698℃, the water temperature is 25℃, and the wiper height is 450mm.

[0222] S6. Heat treatment:

[0223] Step S4: After the casting is completed, the ingot is immediately subjected to a soaking treatment, specifically, a primary soaking treatment and a secondary soaking treatment are performed in sequence.

[0224] The conditions for the first-stage heat treatment are as follows: heating rate 40℃ / h, heating time 10h, holding temperature 410℃, holding time 8h. The conditions for the second-stage heat treatment are as follows: heating rate 7℃ / h, heating time 10h, holding temperature 470℃, holding time 40h.

[0225] S7, rolling deformation:

[0226] The ingot obtained in step S6 was heated to 430°C and then rolled to obtain a plate with a thickness of 80 m. Then, it was stretched to a stretching ratio of 1.5%.

[0227] S8, solution aging:

[0228] The plate obtained in step S7 is subjected to solution treatment, and the process is as follows: heating temperature is 475° C., and heat preservation is performed for 300 min; then quenching is performed in 20° C. water, and the quenching transfer time is 13 s.

[0229] After the above-mentioned solution treatment, a stretching treatment was performed with a stretching ratio of 1.2%.

[0230] After the above-mentioned stretching treatment, artificial aging treatment is carried out: specifically, it is carried out after quenching for 8 hours, the first-level aging is 121°C+4h, and the second-level aging is 154°C+16h.

[0231] After the above processes, the plate is sawn to obtain T7451 state 80mm thickness specification plate, flaw detection and performance testing.

[0232] Quality Inspection :

[0233] The results of the tests were as follows:

[0234] (1) Low magnification of ingot: grain size 2.5.

[0235] (2) Chemical composition: Si 0.03%, Fe 0.05%, Cu 1.90%, Mn 0.01%, Cr 0.01%, Mg 2.13%, Zn 8.30%, Ti 0.03%, Zr 0.12%, Be 0.0009%, Na 0.0001%, single impurity ≤ 0.03%, balance Al.

[0236] (3) Hydrogen content: 0.071 mL / 100 g Al; slag content: 0.006 m 2 / kg.

[0237] (4) Mechanical properties: tensile strength 568 MPa, yield strength 528 MPa, elongation 12%.

[0238] (5) Fracture toughness: 37.47 MPa·m 1 / 2 .

[0239] (6) Stress corrosion resistance: The sample did not crack after 30 days of testing.

[0240] (7) Exfoliation corrosion: Grade EA.

[0241] (8) Fatigue performance: more than 200,000 times.

[0242] (9) Nondestructive testing: meets Class A standards.

[0243] (10) Yield rate: 15 ingots were cast continuously, with a casting yield rate of 93.3%.

[0244] It can be seen that all performances of the product of Example 2 meet the index requirements; in addition, the casting yield is high by continuously repeating the experiment according to Example 2.

[0245] Example 3

[0246] Specifications: Ingot specifications: 450mm thick × 1620mm wide × 4600mm long; plate thickness: 120mm.

[0247] S1. Ingredients:

[0248] Raw materials: Al99.95 grade aluminum ingot, Al99.95 grade copper plate, Al99.9 grade magnesium ingot, Al99.99 grade zinc ingot, AlCu40, AlBe3, AlZr4, AlTi4 intermediate alloys produced from Al99.70 grade aluminum ingot.

[0249] Mix ingredients according to target composition: Please refer to the test results below for ingredient composition.

[0250] S2. Melting:

[0251] The aluminum ingot, copper plate and zinc ingot are heated and melted at a melting temperature of 753°C. After the aluminum ingot, copper and zinc ingot are completely melted, magnesium ingot and various intermediate alloys are added, stirred and slag removed. During this period, sampling analysis and composition adjustment are carried out.

[0252] S3, melt purification:

[0253] After the ingredients in step S2 are adjusted, high-purity argon (purity ≥ 99.999%) is used in the furnace to blow the granular refining agent (same as Example 1) into the melt and refine for 20 minutes; after the powder spray refining in the furnace is qualified, it is transferred to the insulation furnace, and the melt is refined by high-purity argon (purity ≥ 99.999%) through the air-permeable bricks at the bottom of the furnace. The melt temperature during refining is 746°C, the refining time is 40 minutes, and it is allowed to stand for 45 minutes after refining. The hydrogen content of the melt after refining is 0.16mL / 100gAl. After refining through the bottom of the furnace, it is refined by a high-purity argon-chlorine mixed gas (the volume proportion of argon in the mixed gas is 98%) through a rotary degassing device. The hydrogen content of the melt after treatment is 0.063mL / 100gAl. After the above-mentioned online degassing, a 30ppi+50ppi foam ceramic filter plate is used for melt filtration. The slag content after filtration is 0.004m 2 / kg.

[0254] S4. Grain refinement:

[0255] Al-3Ti-0.15C wire was used online for grain refinement, with a dosage of 3.0 kg / t.

[0256] S5. Casting:

[0257] The alloy melt obtained in step S4 is cast to obtain an ingot.

[0258] Casting conditions are as follows: casting speed 46mm / min, water flow 35m 3 / h. root, the aluminum liquid temperature at the end of the flow plate is 700℃, the water temperature is 23℃, and the wiper height is 410mm.

[0259] S6. Heat treatment:

[0260] Step S4: After the casting is completed, the ingot is immediately subjected to a soaking treatment, specifically, a primary soaking treatment and a secondary soaking treatment are performed in sequence.

[0261] The conditions for the first-stage heat treatment are as follows: heating rate 40℃ / h, heating time 10h, holding temperature 410℃, holding time 8h. The conditions for the second-stage heat treatment are as follows: heating rate 7℃ / h, heating time 10h, holding temperature 470℃, holding time 40h.

[0262] S7, rolling deformation:

[0263] The ingot obtained in step S6 was heated to 430°C and then rolled to obtain a plate with a thickness of 120 m. Then, it was stretched to a stretching ratio of 1.5%.

[0264] S8, solution aging:

[0265] The plate obtained in step S7 is subjected to solution treatment, and the process is as follows: heating temperature is 475° C., and heat preservation is performed for 300 min; then quenching is performed in 20° C. water, and the quenching transfer time is 13 s.

[0266] After the above-mentioned solution treatment, a stretching treatment was performed with a stretching ratio of 1.2%.

[0267] After the above-mentioned stretching treatment, artificial aging treatment is carried out: specifically, it is carried out after quenching for 8 hours, the first-level aging is 121°C+4h, and the second-level aging is 154°C+16h.

[0268] After the above processes, the plate is sawn to obtain T7451 state 120mm thickness specification plate, flaw detection and performance testing.

[0269] Quality Inspection :

[0270] The results of the tests were as follows:

[0271] (1) Low magnification of ingot: grain size 2.5.

[0272] (2) Chemical composition: Si 0.02%, Fe 0.04%, Cu 1.93%, Mn 0.01%, Cr 0.01%, Mg 2.10%, Zn 8.28%, Ti 0.03%, Zr 0.12%, Be 0.0012%, Na 0.0001%, single impurity ≤ 0.03%, balance Al.

[0273] (3) Hydrogen content: 0.063mL / 100gAl; slag content: 0.004m 2 / kg.

[0274] (4) Mechanical properties: tensile strength 551 MPa, yield strength 503 MPa, elongation 11%.

[0275] (5) Fracture toughness: 32.14 MPa·m 1 / 2 .

[0276] (6) Stress corrosion resistance: The sample did not crack after 30 days of testing.

[0277] (7) Exfoliation corrosion: Grade EA.

[0278] (8) Fatigue performance: more than 200,000 times.

[0279] (9) Nondestructive testing: meets Class A standards.

[0280] (10) Yield rate: 15 ingots were cast continuously, with a casting rate of 100%.

[0281] It can be seen that all performances of the product of Example 3 meet the index requirements; in addition, the casting yield is high by continuously repeating the experiment according to Example 3.

[0282] Comparative Example 1

[0283] The method is implemented according to Example 1, except that in the casting process of step S5, the casting speed is 57 mm / min, the water flow rate is 42 m 3 / h.root.

[0284] Quality Inspection :

[0285] The results of the tests were as follows:

[0286] (1) Low magnification of ingot: grain size 2.5.

[0287] (2) Chemical composition: Si 0.03%, Fe 0.05%, Cu 1.92%, Mn 0.01%, Cr 0.01%, Mg 2.08%, Zn 8.24%, Ti 0.03%, Zr 0.12%.

[0288] (3) Hydrogen content: 0.072mL / 100gAl; slag content: 0.009m 2 / kg.

[0289] (4) Mechanical properties: tensile strength 595 MPa, yield strength 556 MPa, elongation 14%.

[0290] (5) Fracture toughness: 41.53 MPa·m 1 / 2 .

[0291] (6) Stress corrosion resistance: The sample did not crack after 30 days of testing.

[0292] (7) Exfoliation corrosion: Grade EA.

[0293] (8) Fatigue performance: more than 200,000 times.

[0294] (9) Nondestructive testing: meets Class A standards.

[0295] (10) Yield rate: 5 ingots were cast continuously, with a casting rate of 20%.

[0296] The casting speed of this comparative example was too fast, and the casting forming rate was only about 20%, while the others were scrapped due to cracking due to excessive stress.

[0297] Comparative Example 2

[0298] Implement according to Example 2, except that:

[0299] In the melt purification process of step S3, the bottom of the furnace is ventilated and refined, and then the melt is left to stand for 10 minutes, so that the hydrogen content of the melt is 0.25mL / 100gAl, and the hydrogen content of the melt after online degassing is 0.12mL / 100gAl; the slag content after filtration is 0.032m 2 / kg.

[0300] Quality Inspection :

[0301] The results of the tests were as follows:

[0302] (1) Low magnification of ingot: grain size 2.5.

[0303] (2) Chemical composition: Same as Example 2.

[0304] (3) Hydrogen content: 0.12mL / 100gAl; slag content: 0.032m 2 / kg.

[0305] (4) Mechanical properties: tensile strength 564 MPa, yield strength 521 MPa, elongation 11%.

[0306] (5) Fracture toughness: 33.51 MPa·m 1 / 2 .

[0307] (6) Stress corrosion resistance: The sample did not crack after 30 days of testing.

[0308] (7) Exfoliation corrosion: Grade EA.

[0309] (8) Fatigue performance: 100,000 times on average.

[0310] (9) Nondestructive testing: meets Class A standards.

[0311] The melt hydrogen content and slag content of this comparative example are high, and the fatigue performance is unqualified.

[0312] Comparative Example 3

[0313] Implement according to Example 3, except that:

[0314] In the batching process of step S1, the alloy composition is changed, and the specific details refer to the post-culture chemical composition test results.

[0315] Quality Inspection :

[0316] The results of the tests were as follows:

[0317] (1) Low magnification of ingot: grain size 2.5.

[0318] (2) Chemical composition: Si 0.02%, Fe 0.04%, Cu 1.86%, Mn 0.01%, Cr 0.01%, Mg 1.62%, Zn 7.46%, Ti 0.03%, Zr 0.12%, Be 0.0012%, Na 0.0001%, single impurity ≤ 0.03%, balance Al.

[0319] (3) Hydrogen content: 0.062mL / 100gAl; slag content: 0.005m 2 / kg.

[0320] (4) Mechanical properties: tensile strength 510 MPa, yield strength 435 MPa, elongation 16%.

[0321] (5) Fracture toughness: 36.09 MPa·m 1 / 2 .

[0322] (6) Stress corrosion resistance: The sample did not crack after 30 days of testing.

[0323] (7) Exfoliation corrosion: Grade EA.

[0324] (8) Fatigue performance: more than 200,000 times.

[0325] (9) Nondestructive testing: meets Class A standards.

[0326] The contents of the main elements Mg and Zn in this comparative example are relatively low, and the mechanical properties are unqualified.

[0327] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing an aviation aluminum alloy sheet, characterized in that: The following steps are involved: S1. Ingredients: The raw materials are batched according to the target alloy composition; in, In terms of mass percentage, the target alloy comprises: Si: ≤0.04%; Fe: ≤0.07%; Cu: 1.7%~2.0%; Mn: ≤0.02%; Mg: 1.8%~2.2%; Cr:≤0.02%; Zn: 7.7%~8.5%; Ti: ≤0.05%; Zr:0.05%~0.15%; Be: 0.0005%~0.005%; Na: ≤0.0003%; Single impurity: ≤0.03%; The balance is Al; The raw materials include: aluminum ingots, copper, magnesium ingots, zinc ingots, Al-Cu master alloys, Al-Zr master alloys, Al-Ti master alloys, and Al-Be master alloys; S2. Melting: The raw materials are smelted to obtain an alloy melt; S3, melt purification: In the furnace, the granular refining agent is first blown into the melt by gas medium 1 for powder spray refining in the furnace; then the melt is transferred to the holding furnace, and the melt is refined by gas medium 2 through the air-permeable bricks at the bottom of the furnace, and then allowed to stand after refining; then the melt is degassed and refined by the rotary degassing device; then, it is filtered to obtain a purified melt; in, The gas medium 1 is argon, and the purity of the argon is ≥ 99.999%; The gas medium 2 is argon gas, and the purity of the argon gas is ≥ 99.999%; The gas used for degassing and refining is an argon-chlorine mixed gas; the purity of the gas is ≥99.999%; the volume proportion of argon in the argon-chlorine mixed gas is 95% to 99.5%; S4. Grain refinement: Grain refinement was performed online using Al-3Ti-0.15C wire; S5. Casting: Casting the alloy melt obtained in step S4 to obtain an ingot; The casting conditions are as follows: casting speed 40-55 mm / min, water flow 30-60 m 3 / h. Root, aluminum liquid temperature at the end of the flow plate is 695~715℃, water temperature is 22~28℃, and wiper height is 200~500mm; S6. Heat treatment: The ingot obtained in step S5 is subjected to primary soaking treatment and secondary soaking treatment in sequence; The conditions of the first-stage heat treatment are as follows: heating rate 30-80°C / h, holding temperature 380-420°C, holding time 5-12h; The conditions of the secondary heat treatment are as follows: heating rate 5-20°C / h, holding temperature 465-475°C, holding time 30-50h; S7, rolling deformation: The ingot obtained in step S6 is heated, rolled into a plate, and stretched to obtain a plate; S8, solution aging: The plate obtained in step S7 is subjected to solution treatment, stretching treatment, and aging treatment to obtain an aviation aluminum alloy plate.

2. The preparation method according to claim 1, characterized in that: Step S2 specifically includes: The aluminum ingot, copper and zinc ingot are heated and melted, and then magnesium ingot, Al-Cu master alloy, Al-Zr master alloy, Al-Ti master alloy and Al-Be master alloy are added, smelted and slag removed to obtain alloy melt; The heating and melting temperature is 730-770°C.

3. The preparation method according to claim 1, characterized in that: In step S3, when the melt is refined by gas medium 2 through the air-permeable bricks at the bottom of the furnace, the melt temperature during refining is 730-750°C, the refining time is 20-40 minutes, and the standing time is ≥45 minutes.

4. The preparation method according to claim 1, characterized in that: In step S3, the filtration is performed using a 30ppi+50ppi or 40ppi+60ppi ceramic filter plate.

5. The preparation method according to claim 1, characterized in that: In step S4, the amount of the Al-3Ti-0.15C wire used is 2.0-4.0 kg / t.

6. The preparation method according to claim 1, characterized in that: In step S5, the specifications of the cast ingot are as follows: thickness 400-520 mm, width 1500-2250 mm, length 4000-8000 mm.

7. The preparation method according to claim 1, characterized in that: In step S6: The heating temperature is 400-450°C; The stretching ratio of the stretching treatment is 1% to 3%.

8. The preparation method according to claim 1, characterized in that: In step S7: The solution treatment temperature is 465-480°C, and the holding time is 90-450min; the solution quenching transfer time is less than 15s, and the quenching water temperature is 10-30°C; The stretching ratio of the stretching treatment is 0.5% to 1.5%.

9. The preparation method according to claim 1, characterized in that: In step S7, the artificial aging treatment is performed 2 to 48 hours after solution quenching; The artificial aging treatment includes two-stage aging treatment; wherein, the conditions of the first-stage aging treatment are: temperature 121° C., time 4 to 6 hours; the conditions of the second-stage aging treatment are: temperature 148 to 160° C., time 10 to 30 hours.

10. An aviation aluminum alloy plate, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Al-Zn-Mn alloy profile for rail transit vehicle body and preparation method thereof

    CN108251723A

  • Ultrahigh-strength aviation aluminum alloy and preparation method thereof

    CN111455239A

  • Scandium-containing ultrahigh-strength aluminum alloy for aerospace and manufacturing method thereof

    CN112646997A

  • Preparation method of high-strength corrosion-resistant 7xxx aluminum alloy plate for aviation

    CN113528866A

  • Preparation method of high-strength and high-toughness 7-series aluminum alloy thick plate

    CN115354177A

Cited By

  • Processing method of wrought aluminum alloy

    CN120443075A

  • Aviation aluminum alloy material and preparation process thereof

    CN121183180A

  • A method for preparing large-size, high-performance aerospace aluminum alloy thick plates

    CN122564360A